calculus infography
Avatar
CalculusPop
CalculusPop
Hey, let's solve some calculus with CalculusPop
 
Differentiation

Differentiation from first principles is a method used to find the derivative of a function by directly applying the definition of a derivative. This method is often used when the function is not easily differentiable using standard rules or techniques.

The general formula for finding the derivative of a function f(x) from first principles is:

f'(x) = \lim_{{h \to 0}} \frac{f(x + h) - f(x)}{h}

To apply this formula and find the derivative of a function, follow these steps:

Step 1: Identify the function f(x) for which you want to find the derivative.

Step 2: Write down the general formula for differentiation from first principles.

Step 3: Substitute the function f(x) into the formula.

Step 4: Simplify the expression by expanding and combining like terms.

Step 5: Take the limit as h approaches 0 by substituting h = 0 into the expression.

Step 6: Evaluate the limit to find the derivative of the function.

Step 7: Verify the result by comparing it with known derivative rules or using other methods to find the derivative.

By following these steps, you can find the derivative of a function using the differentiation from first principles method. This method provides a rigorous way to find the derivative of a function by directly applying the definition of a derivative.

Question 1:
Find the derivative of f(x) = 3x^2 - 2x + 5 from first principles.

Solution 1:
Given function: f(x) = 3x^2 - 2x + 5

To find the derivative from first principles, we use the definition of derivative:

f'(x) = \lim_{{h \to 0}} \frac{f(x+h) - f(x)}{h}

Substitute f(x) into the formula:

f'(x) = \lim_{{h \to 0}} \frac{3(x+h)^2 - 2(x+h) + 5 - (3x^2 - 2x + 5)}{h}

Expand and simplify the expression:

f'(x) = \lim_{{h \to 0}} \frac{3(x^2 + 2xh + h^2) - 2x - 2h + 5 - 3x^2 + 2x - 5}{h}

f'(x) = \lim_{{h \to 0}} \frac{3x^2 + 6xh + 3h^2 - 2x - 2h + 5 - 3x^2 + 2x - 5}{h}

f'(x) = \lim_{{h \to 0}} \frac{6xh + 3h^2 - 2h}{h}

f'(x) = \lim_{{h \to 0}} 6x + 3h - 2

f'(x) = 6x - 2

Therefore, the derivative of f(x) = 3x^2 - 2x + 5 is f'(x) = 6x - 2.

Question 2:
Find the derivative of g(x) = 4x^3 + 2x^2 - x from first principles.

Solution 2:
Given function: g(x) = 4x^3 + 2x^2 - x

To find the derivative from first principles, we use the definition of derivative:

g'(x) = \lim_{{h \to 0}} \frac{g(x+h) - g(x)}{h}

Substitute g(x) into the formula:

g'(x) = \lim_{{h \to 0}} \frac{4(x+h)^3 + 2(x+h)^2 - (x+h) - (4x^3 + 2x^2 - x)}{h}

Expand and simplify the expression:

g'(x) = \lim_{{h \to 0}} \frac{4(x^3 + 3x^2h + 3xh^2 + h^3) + 2(x^2 + 2xh + h^2) - x - h - 4x^3 - 2x^2 + x}{h}
g'(x) = \lim_{{h \to 0}} \frac{4x^3 + 12x^2h + 12xh^2 + 4h^3 + 2x^2 + 4xh + 2h^2 - x - h - 4x^3 - 2x^2 + x}{h}
g'(x) = \lim_{{h \to 0}} \frac{12x^2h + 12xh^2 + 4h^3 + 4xh + 2h^2 - h}{h}
g'(x) = \lim_{{h \to 0}} 12x^2 + 12xh + 4h^2 + 4x + 2h - 1
g'(x) = 12x^2 + 4x - 1

Therefore, the derivative of g(x) = 4x^3 + 2x^2 - x is

g'(x) = 12x^2 + 4x - 1

Question 3:
Find the derivative of h(x) = sin(x) from first principles.

Solution 3:
Given function: h(x) = \sin(x)

To find the derivative from first principles, we use the definition of derivative:

h'(x) = \lim_{{h \to 0}} \frac{h(x+h) - h(x)}{h}

Substitute h(x) into the formula:

h'(x) = \lim_{{h \to 0}} \frac{\sin(x+h) - \sin(x)}{h}

Apply the angle sum identity for sine function:

h'(x) = \lim_{{h \to 0}} \frac{\sin(x)\cos(h) + \cos(x)\sin(h) - \sin(x)}{h}

Simplify the expression:

h'(x) = \lim_{{h \to 0}} \frac{\sin(x)\cos(h) + \cos(x)\sin(h) - \sin(x)}{h}
h'(x) = \lim_{{h \to 0}} \frac{\sin(x)(\cos(h) - 1) + \cos(x)\sin(h)}{h}
h'(x) = \lim_{{h \to 0}} \frac{\sin(x)(\cos(h) - 1)}{h} + \lim_{{h \to 0}} \frac{\cos(x)\sin(h)}{h}
h'(x) = \sin(x)\lim_{{h \to 0}} \frac{\cos(h) - 1}{h} + \cos(x)\lim_{{h \to 0}} \frac{\sin(h)}{h}

Using the limit definition of derivative for sine function, we know:
\lim_{{h \to 0}} \frac{\sin(h)}{h} = 1

Therefore, the derivative of h(x) = sin(x) is h'(x) = cos(x).

Question 4:
Find the derivative of k(x) = \sqrt{x} from first principles.

Solution 4:
Given function: k(x) = \sqrt{x}

To find the derivative from first principles, we use the definition of derivative:
k'(x) = \lim_{{h \to 0}} \frac{k(x+h) - k(x)}{h}

Substitute k(x) into the formula:
k'(x) = \lim_{{h \to 0}} \frac{\sqrt{x+h} - \sqrt{x}}{h}

Rationalize the numerator:
k'(x) = \lim_{{h \to 0}} \frac{(\sqrt{x+h} - \sqrt{x})(\sqrt{x+h} + \sqrt{x})}{h(\sqrt{x+h} + \sqrt{x})}
k'(x) = \lim_{{h \to 0}} \frac{(x+h) - x}{h(\sqrt{x+h} + \sqrt{x})}
k'(x) = \lim_{{h \to 0}} \frac{h}{h(\sqrt{x+h} + \sqrt{x})}
k'(x) = \lim_{{h \to 0}} \frac{1}{\sqrt{x+h} + \sqrt{x}}
k'(x) = \frac{1}{2\sqrt{x}}

Therefore, the derivative of k(x) = √x is k'(x) = 1/(2√x).

Question 5:
Find the derivative of y(x) = e^xfrom first principles.

Solution 5:
Given function: y(x) = e^x

To find the derivative from first principles, we use the definition of derivative:
y'(x) = \lim_{{h \to 0}} \frac{y(x+h) - y(x)}{h}

Substitute y(x) into the formula:
y'(x) = \lim_{{h \to 0}} \frac{e^{x+h} - e^x}{h}

Apply the properties of exponential functions:
y'(x) = \lim_{{h \to 0}} \frac{e^x \cdot e^h - e^x}{h}
y'(x) = \lim_{{h \to 0}} \frac{e^x (e^h - 1)}{h}

Since \lim_{{h \to 0}} \frac{e^h - 1}{h} = 1,
y'(x) = e^x

Therefore, the derivative of y(x) = e^x is y'(x) = e^x.

Questions

1. \frac{d}{dx}(f(x)g(x))

2. \frac{d}{dx}(3x^2 \cdot \sin(x))

3. \frac{d}{dx}(e^x \cdot \cos(x))

4. \frac{d}{dx}(2x \cdot \ln(x))

5. \frac{d}{dx}(x^3 \cdot e^{2x})

6. \frac{d}{dx}(4x \cdot \tan(x))

7. \frac{d}{dx}(6x^2 \cdot \sqrt{x})

8. \frac{d}{dx}(\ln(x) \cdot e^x)

9. \frac{d}{dx}(2x^3 \cdot \sin(2x))

10. \frac{d}{dx}(x \cdot \cos(x))

11. \frac{d}{dx}(4x^2 \cdot e^x)

12. \frac{d}{dx}(e^{3x} \cdot \tan(x))

13. \frac{d}{dx}(5x \cdot \ln(2x))

14. \frac{d}{dx}(x^4 \cdot \cosh(x))

15. \frac{d}{dx}(e^{-x} \cdot \sin(x))

Answer:

1. g(x)+f(x)g'(x)

2. 6x\sin(x)+3x^2\cos(x)

3. e^x\cos(x)-e^x\sin(x)

4. 2\ln(x)+2

5. 3x^2e^{2x}+2x^3e^{2x}

6. 4\tan(x)+4x\sec^2(x)

7. 12x\sqrt{x}+3x^2\sqrt{x}

8. \frac{1}{x}e^x+\ln(x)e^x

9. 6x^2\sin(2x)+4x^3\cos(2x)

10. \cos(x)-x\sin(x)

11. 4x^2e^x+8xe^x

12. 3e^{3x}\tan(x)+e^{3x}\sec^2(x)

13. 5\ln(2x)+5 [\frac{1}{x}]

14. 4x^3\cosh(x)+x^4\sinh(x)

15. -e^{-x}\sin(x)-e^{-x}\cos(x)

Previous Lesson
Classroom: Differentiation of sine and cosine functions
Next Lesson
Differentiate - x^(1/2)

Classroom: Differentiation from first principles

f'(x) = \lim_{{h \to 0}} \frac{f(x + h) - f(x)}{h}

Calculus Archives

Useful Calculus links

Differential Calculus Playground
The "Differential Calculus Playground" is a valuable educational tool that allows users to test their...
Differentiate 3In5x With Steps
To differentiate the expression 3ln5x with respect to x, we will use the chain rule of differentiation....
Classroom: Differentiation of sine and cosine functions
The differentiation of sine and cosine functions involves finding the derivatives of these trigonometric...
Differentiate tan(3x) With Steps
To differentiate the function tan(3x) with respect to x, we must use the chain rule. The derivative of...
Classroom: Differentiation from first principles
Differentiation from first principles is a method of finding the derivative of a function by using the...
Ads Blocker Image Powered by Code Help Pro

Ads Blocker Detected!!!

We have detected that you are using extensions to block ads. Please support us by disabling these ads blocker.

Powered By
100% Free SEO Tools - Tool Kits PRO